−808 nm-activated Ca2+ doped up-conversion nanoparticles that release no inducing liver cancer cell (HepG2) apoptosis. (1st April 2022) - Fa, Xinmeng; Lin, Shaowei; Yang, Jianghua; Shen, Chong; Liu, Yuanli; Gong, Yongyang; Qin, Aimiao; Ou, Jun; Resch-Genger, Ute
Abstract: A near-infrared (NIR) light-triggered release method for nitric oxide (NO) was developed utilizing core/shell NaYF4 : Tm/Yb/Ca@NaGdF4 : Nd/Yb up-conversion nanoparticles (UCNPs) bearing a mesoporous silica (mSiO2 ) shell loaded with the NO donor S-nitroso-N-acetyl-DL-penicillamine (SNAP). To avoid overheating in biological samples, Nd 3+ was chosen as a sensitizer, Yb 3+ ions as the bridging sensitizer, and Tm 3+ ions as UV-emissive activator while co-doping with Ca 2+ was done to enhance the luminescence of the activator Tm 3+ . NO release from SNAP was triggered by an NIR-UV up-conversion process, initiated by 808 nm light absorbed by the Nd 3+ ions. NO release was confirmed by the Griess method. Under 808 nm irradiation, the viability of the liver cancer cell line HepG2 significantly decreased with increasing UCNPs@mSiO2 -SNAP concentration. For a UCNPs@mSiO2 -SNAP concentration of 200 μ g ml −1, the cell survival probability was 47%. These results demonstrate that UCNPs@mSiO2 -SNAP can induce the release of apoptosis-inducing NO by NIR irradiation.